Implementasi Pondok Baca Dalam Peningkatan Minat Membaca Siswa SDN 105322 Desa Mesjid, Kecamatan Batangkuis - Lia Putri Ashari Lubis; Ahmad Sopiyan; Juwita Rahayu Manurung; Novia Asri Nasution (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Indonesia is one of the countries with a fairly low literacy rate. Most Indonesian people do not realize the importance of literacy. Even some people do not understand what literacy is. Literacy is a form of reading, writing, and listening activities, which are accompanied by critical thinking so that they are accustomed to solving problems. Reading and writing both have not become a culture in Indonesia. In fact, the development of science and culture must start from both. The reading hut located at SDN 105322 Desa Mesjid has not been functioning properly. That’s why KKN 214 UINSU participants are trying to implement the reading cottage which will certainly increase interest in reading in children, especially students of SDN 105322 Desa Mesjid. Keywords : Interest, Reading, Literacy, Kids